Analysis of threats to South American flora and its implications for conservation - Ramírez Villegas, Julián Armando; Jarvis, Andy; Touval, Jerome L. (2014)
Study: A set of seven threats to natural ecosystems derived from a previous study (Jarvis et al. 2010), combined with a dataset of occurrences from 16,339 species, and also with the World Database of Protected Areas were used to analyse the patterns of threats to flora in South America and its conservation. Data: Data tables with results of assessment of threat and conservation level for all South American plant species for which there was data in GBIF.